Salivary Antioxidant Barrier, Redox Status, and Oxidative Damage to Proteins and Lipids in Healthy Children, Adults, and the Elderly - Mateusz Maciejczyk (Oxidative Medicine and Cellular Longevity, 2019)
Despite the proven role of oxidative stress in numerous systemic diseases and in the process of aging, little is still known about the salivary redox balance of healthy children, adults, and the elderly. Our study was the first to assess the antioxidant barrier, redox status, and oxidative damage in nonstimulated (NWS) and stimulated (SWS) saliva as well as blood samples of healthy individuals at different ages. We divided 90 generally healthy people into three equally numbered groups based on age: 2–14 (children and adolescents), 25–45 (adults), and 65–85 (elderly people). Antioxidant enzymes (salivary peroxidase (Px), glutathione peroxidase (GPx), catalase (CAT), and superoxide dismutase-1 (SOD)), nonenzymatic antioxidants (reduced glutathione (GSH) and uric acid (UA)), redox status (total antioxidant capacity (TAC), total oxidant status (TOS), and oxidative stress index (OSI)), and oxidative damage products (advanced glycation end products (AGE), advanced oxidation protein products (AOPP), and malondialdehyde (MDA)) were evaluated in NWS and SWS as well as in erythrocyte/plasma samples. We demonstrated that salivary and blood antioxidant defense is most effective in people aged 25–45. In the elderly, we observed a progressive decrease in the efficiency of central antioxidant systems (↓GPx, ↓SOD, ↓GSH, and ↓TAC in erythrocytes and plasma vs. adults) as well as in NWS (↓Px, ↓UA, and ↓TAC vs. adults) and SWS (↓TAC vs. adults). Both local and systemic antioxidant systems were less efficient in children and adolescents than in the group of middle-aged people, which indicates age-related immaturity of antioxidant mechanisms. Oxidative damage to proteins (↑AGE, ↑AOPP) and lipids (↑MDA) was significantly higher in saliva and plasma of elderly people in comparison with adults and children/adolescents. Of all the evaluated biomarkers, only salivary oxidative damage products generally reflected their content in blood plasma. The level of salivary redox biomarkers did not vary based on gender.